The friendships of John Adams, 1774-1801 : the art of politics - Macpherson, Jamie (New York, NY : Routledge, 2024)
"This book presents the first extended analysis of the friendship network of John Adams, forged during his lengthy public career from 1774-1801. While scholars have considered historic friendships, this monograph examines Adams's friendship network within a generation of revolutionaries. The six friendships explored exemplify the diversity of political interaction: primary friendship (Abigail), intimate confidence (Rush), political alliance (Gerry), emergent rivalry (Jefferson), the politics of personal difference (Mercy Otis Warren), and idolised revolutionary (Samuel Adams). This work positions friendship at the heart of the historian's craft; reconstructing historic relationships and considering the evolution of each dyad to examine the tensions, candour, intimacy, and forms of alliance in each. Adams's impassioned epistles present a window into his private ruminations. John Adams's expectation of friendship changed at each stage of his career: Through 1774-1801, Adams entreated support from friends, debated issues pertaining to politics, diplomacy, and the national interest, sought comfort from intimates, and lamented divisions from former friends. For John Adams, friendship represented the art of politics. This volume will be of value to students and scholars alike interested in American history, political history and social and cultural history"--
The Continental Congress, 1774-1778 -- Diplomacy, 1778-1788 -- Executive Service, 1788-1801.
Keywords: Adams, John, -- 1735-1826 -- Friends and associates; Presidents -- United States -- Biography; United States -- Politics and government -- 1775-1783.; United States -- Politics and government -- 1783-1809.; HISTORY / United States / Colonial Period (1600-1775); HISTORY / United States / Revolutionary Period (1775-1800); HISTORY / Social History